Strategi Pengembangan Sumber Daya Manusia dengan Pendekatan Pola Komunikasi Efektif dalam Mewujudkan Konsep Malang Smart City - Endra Yuafanedi Arifianto (Program Studi Ilmu Komunikasi FISIP Universitas Syiah Kuala, 2017)
The concept of a smart city has an agenda to strengthen urban management through the use of information and communication technology. Related to that, the Malang City Government continues to be innovative and creative to support smart city program. One of the breakthroughs of the Office of Communication and Informatics of Malang City to support Malang Smart City program is by forming Forum of Public Information Group (KIM). The forum consists of people who are active in information sectors ranging from urban village to city levels. This study looks at the development of community human resources in the forum of KIM Kota Malang by using SWOT analysis, namely internal analysis (strengths and weaknesses) and external (opportunities and threats). The result of the research shows that KIM Forum of Malang City is an asset of Malang City Government that must be developed because it has a strategic role in bridging information from the city government to the urban community through effective communication skills. Human resource development strategy is needed to support Malang Smart City program.